Determinan Kepatuhan Wajib Pajak Orang Pribadi di Wilayah Jakarta Barat - Tania Pretty Cia; Ida Bagus Nyoman Sukadana (Media Bisnis, 2021)
This research was to examine the effect of independent variables (awareness of paying taxes, tax sanctions, tax authorities' attitudes, subjective norms, knowledge of tax regulations, perceptions of the effectiveness of the tax system, willingness to pay taxes and service quality) on the dependent variable (taxpayer compliance). The sample of this research is an individual who is registered at the KPP West Jakarta. Data collection was done by distributing questionnaires via google form. The data collection technique in this study was convenience sampling. The data analysis process in this study uses the SPSS 25 program. The results of this research indicate that tax sanctions and perceptions of the effectiveness of the taxation system affect taxpayer compliance because if the increasingly stringent tax sanctions and a high perception of the effectiveness of the taxation system owned by taxpayers, it will increasingly encourage taxpayers to comply with their tax obligations. While the awareness of paying taxes, the attitude of the tax authorities, subjective norms, knowledge of tax regulations, willingness to pay taxes and service quality have no effect on taxpayer compliance.